RDM1 plays an oncogenic role in clear cell renal cell carcinoma potentially by modulating MCM2 - Xiuming Li; Hui Liu; Yujie Wei; Anxin Wang; Chengcheng Lv; Yu Zeng (Scientific Reports)
Abstract Kidney cancer may result from different gene mutations, each contributing to different histological subtypes and prognoses. RAD52 motif-containing 1 (RDM1) regulates multiple cancer pathways, but its role in ccRCC is unknown to date. According to our results, RDM1 expression increased in ccRCC cells, which was correlated to poor survival in ccRCC patients. Knockdown of RDM1 arrested the cell cycle, promoted cell apoptosis, and apparently suppressed ccRCC cell growth in vitro and in vivo. From the mechanism perspective, RDM1 drove MCM2 to modulate ccRCC cell cycle. Thus, RDM1 inhibition blocks cell cycle progression, suppresses ccRCC cell growth, and is a promising approach for treating ccRCC.